Local border traffic as an efficient tool for developing cross-border cooperation - Gumenyuk Ivan; Kuznetsova Tatyana; Osmolovskaya Lidiya (Baltic Region, 2017)
Local border traffic (LBT) is a tool for cooperation between the EU member states and neighbouring countries. It emerged as a measure to mitigate the barrier effect of the EU’s external border. In 2006, the European Parliament authorised the EU member states to conclude bilateral agreements on a simplified border crossing regime in border areas. This article analyses local border traffic as a cross-border cooperation tool. The territory described in the study includes the external borders of the EU (and Norway) with the Russian Federation and the Republic of Belarus. The article will be of interest to specialists in international and, particularly, in cross-border cooperation. The authors analyse the mechanism of local border traffic and identify possible trends based on the general socioeconomic situation and foreign policy background in Russia, Belarus, and the EU (Norway). The article employs the cartographic method to enhance the visual component of the study. It is concluded that the LBT mechanism is effective and it has a positive effect on the development of border contacts between countries. There is a need to continue the dialogue between Russia, Belarus and the EU countries on both expanding the geographical scope of the LBT mechanism and ensuring its qualitative development.